BMI and Mortality in UK Biobank: Revised Estimates Using Mendelian Randomization. Issue 11 (25th October 2018) - Wade, Kaitlin H.; Carslake, David; Sattar, Naveed; Davey Smith, George; Timpson, Nicholas J.
Abstract : Objective: The aim of this study was to obtain estimates of the causal relationship between BMI and mortality. Methods: Mendelian randomization (MR) with BMI‐associated genotypic variation was used to test the causal effect of BMI on all‐cause and cause‐specific mortality in UK Biobank participants of White British ancestry. Results: MR analyses supported a causal association between higher BMI and greater risk of all‐cause mortality (hazard ratio [HR] per 1 kg/m 2 : 1.03; 95% CI: 0.99‐1.07) and mortality from cardiovascular diseases (HR: 1.10; 95% CI: 1.01‐1.19), specifically coronary heart disease (HR: 1.12; 95% CI: 1.00‐1.25) and those excluding coronary heart disease/stroke/aortic aneurysm (HR: 1.24; 95% CI: 1.03‐1.48), stomach cancer (HR: 1.18; 95% CI: 0.87‐1.62), and esophageal cancer (HR: 1.22; 95% CI: 0.98‐1.53), and a decreased risk of lung cancer mortality (HR: 0.96; 95% CI: 0.85‐1.08). Sex stratification supported the causal role of higher BMI increasing bladder cancer mortality risk (males) but decreasing respiratory disease mortality risk (males). The J‐shaped observational association between BMI and mortality was visible with MR analyses, but the BMI at which mortality was minimized was lower and the association was flatter over a larger BMI range. Conclusions: Results support a causal role of higher BMI in increasing the risk of all‐cause mortality and mortality from several specific causes.